Development and application of a linear polyamidoamine-SiRNA delivery system - Fathi, Zainab H (2018)
Spleen tyrosine kinase (Syk) plays a critical role in regulation of immune and inflammatory responses. The important role of Syk in inflammatory signalling cascades has led to the development of therapeutic agents designed to knock down Syk gene as novel therapeutic agents for allergic diseases (1). This thesis investigated the role of siRNA in Syk silencing using the newly developed RBL reporter systems as an in vitro model to study degranulation. Lack of an efficient and safe non-viral delivery systems has hindered the progress of siRNA into clinics. The ideal properties of the siRNA-nanoparticles for efficient delivery would require the following properties, 1. Safe with low toxic effects to the cells (non-toxic polymers and nanoparticle components); 2. Compact and well-condensed nanoparticles (thiol crosslinking and PEG); 3. Small size (20–200 nm) for easy cellular internalization (thiol crosslinking and PEG); 4. Less interaction with the environment to enable access to the target cells (PEG); 5. Neutral surface charged and sterically stable siRNA polyplexes with bio-reducible characteristics essentially required for in vivo delivery (Thiol-modified siRNA and PEG). Hence, low-toxicity linear cationic polyamidoamine (PAA) consisting of a mixture of PEGylated copolymer (CP) and non-PEGylated homopolymer (HP) were used for the formulation of the PAA-siRNA nanoparticles. This system has previously been shown to assemble into small sterically stabilised particles with reducible crosslinks. A cross-linked system of HP and HP-CP blends showed complete incorporation of thiolated siRNA during gel electrophoresis, and produced particle size less than that of non-thiolated siRNA as determined using a dynamic light scattering technique. A degranulation inhibition assay revealed that these cross-linked polyplexes prepared using thiol-modified siRNA efficiently inhibited release of fluorescent granules (NPY-mRFP) from the genetically modified RBL-2H3 NPY-mRFP cell line. There was no cytotoxicity associated with this delivery system. By using HP/SH-siRNA nanoparticle, a remarkable dose-dependent Syk gene silencing (~80%) was observed on mRNA level using RT-qPCR. Finally, the HP/SH-siRNA polyplexes produced also showed a significant reduction in Syk protein levels using Western blotting. From the data obtained it is concluded that cross-linked siRNA polyplexes prepared with thiolated siRNA are safe, effective and easy to prepare for future siRNA in vivo gene silencing applications to treat allergic diseases.